Observation of the failure mechanism for diamond-like carbon film on stainless steel under tensile loading - Kim, Hyun-Jong; Moon, Myoung-Woon; Kim, Dong-Ik; Lee, Kwang-Ryeol; Oh, Kyu Hwan (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
This study investigated the fracture behaviour of cohesive cracking and subsequent buckling delamination at the interface between a diamond-like carbon (DLC) film and a stainless steel substrate during tension testing. It was revealed by cross-sectional analysis with a focused ion beam system that spallation of the DLC film was caused by interfacial cracking and the subsequent kinking into a thin film layer. Interfacial adhesion strength was estimated by the spatted crack width, which shows that the adhesion of the DLC coating was considerably improved by increasing the negative bias voltage during Ar plasma etching prior to the film deposition. (c) 2007 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: THIN-FILMS; COATINGS; ADHESION; CRACKING; DECOHESION; HYDROXYAPATITE; INTERFACE